2015
DOI: 10.1158/1535-7163.mct-14-0538-t
|View full text |Cite
|
Sign up to set email alerts
|

p53 Family Members Regulate Phenotypic Response to Aurora Kinase A Inhibition in Triple-Negative Breast Cancer

Abstract: Triple-negative breast cancer (TNBC) is an aggressive disease with a poor prognosis. Advances in the treatment of TNBC have been hampered by the lack of novel effective targeted therapies. The primary goal of this study was to evaluate the efficacy of targeting Aurora kinase A (AurA), a key regulator of mitosis, in TNBC models. A secondary objective was to determine the role of the p53 family of transcriptional regulators, commonly mutated in TNBC, in determining the phenotypic response to the AurA inhibitor a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
49
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 51 publications
9
49
0
Order By: Relevance
“…In some models, if p53 activity is lost, cells appear to be more sensitive to Aurora kinase A and B inhibition [26]. However in a triple negative breast cancer model, knockdown of wildtype p53 abrogated the alisertib apoptotic activity [15]. Assessment of p53 by immunoblotting in our studies demonstrated an induction of p53 in the sensitive p53 WT HCT116 CRC cell line at all time points, however after 48 hours of treatment with alisertib the induction is more pronounced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some models, if p53 activity is lost, cells appear to be more sensitive to Aurora kinase A and B inhibition [26]. However in a triple negative breast cancer model, knockdown of wildtype p53 abrogated the alisertib apoptotic activity [15]. Assessment of p53 by immunoblotting in our studies demonstrated an induction of p53 in the sensitive p53 WT HCT116 CRC cell line at all time points, however after 48 hours of treatment with alisertib the induction is more pronounced.…”
Section: Discussionmentioning
confidence: 99%
“…This treatment also resulted in upregulation of p53, p21 and p27. Furthermore, in triple negative breast cancer alisertib demonstrated antiproliferative effects regardless of subtype, however there was a trend whereby increased p53 mRNA expression associated with increased sensitivity to alisertib [15]. In addition, in combination with dexamethasone, doxorubicin, or bortezomib, alisertib induced synergistic./additive activity in vitro [16].…”
Section: Introductionmentioning
confidence: 99%
“…Independent of cell cycle checkpoints, we also sought to determine whether senescence causes resistance to KW-2450 in TNBC cells, as reported by others (28, 29). We did not see significant senescence induction in any TNBC cells treated with 0.5 μM KW-2450 for 5 days; however, we did see induction of senescence at higher concentrations (1, 4 μM) and with longer exposure to KW-2450 (for 10 days) (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Another report shows that triple‐negative breast cancer cells with a mutation in p53 and increased p53 expression are more sensitive than other breast cancer cell lines to ENMD‐2076, another Aurora‐A inhibitior . Consistently, induction of apoptosis in response to MLN8237 exposure is dependent on activity of the p53 family . In addition, the latelet‐activating factor acetylhydrolase and GTP‐binding nuclear protein Ran contribute to development of resistance to Aurora‐A/B inhibitor ZM447439 related to p53 in HCT116 colon cancer cells .…”
Section: Targeting Aurora‐a Kinasementioning
confidence: 82%